The Used of Google Classroom during Covid 19 Pandemic - Etika Dewi Kusumaningtyas (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
Nowadays, worldwide still struggling with a pandemic of a virus that is called novel coronavirus. This virus has expanded from 2019 till now. Subsequently, governments decide on modifying each single scope including on education. Government restricts face to face meeting toward cutting off Covid 19 expanses. Government has to provide a new rule of teaching the learning process. This situation has an enormous encounter between teacher and student; they should conduct a teaching learning process by online. Thus Google classroom by Google is one of one stop platforms in the electronic learning process. It assists both teacher and student to conduct online class and they can arrange assignments generously by utilizing Google classroom. The method that was employed in this research was a library research. Arikunto stated that literature studies in research are methods of collecting data by seeking information through books, newspapers, magazines and other literature that aims to form a theoretical foundation (Arikunto, 2006). The entire research stands on discussing the effectiveness of Google Classroom by Google both qualitative research and quantitative research. This condition defines that online learning has a significant role in pandemic. Since the research collects the entire journal, the researcher obtained that this research clearly clarifies that Google classrooms effectively support online learning in Covid 19 pandemic.